Analisis Penerapan Sharian Compliance Pada Produk Pembiayaan Mikro BSI KUR Di Bank Syariah Indonesia - Uswatun Hasanah; Nurul Fitriani; Kharis Fadlullah Hana (Institut Agama Islam Negeri Parepare, 2022)
Implementation of Sharia Compliance is an absolute requirement that must be implemented by Sharia Banking by using the fatwa of the MUI DSN as a measuring instrument for compliance with Sharia Principles. However, in practice it is not as easy as what is discussed in theory, there are still many incidents that are prone to syar'i errors. The purpose of this study was to analyze the suitability of the application of Sharia Compliance to the BSI KUR-Mikro financing product at Bank Syariah Indonesia. This study uses a qualitative descriptive method that retrieves information trhough interviews. Data collection was obtained through interviews with employees and customers of Bank Syariah Indonesia Kudus branch. The results of this study indicate that: firts, Bank Syariah Indonesia has complied with sharia principles, because all transactions and activities are based on the fatwa of DSN MUI, and are supervised by DPS. Second, BSI KUR Micro financing products are already compliant with sharia principles because, not all businesses can be financed by BSI KUR Micro, but only businesses that have the potential to be halal. These results provide recommendations for further researchers to analyze sharia compliance not only from employee and customer assessments, but also to see sharia compliance through the Sharia Supervisory Board (DPS) directly. Keywords: Sharia Compliance, Islamic Banking, BSI KUR Micro